Meningkatkan Kemampuan Menulis Puisi Melalui Metode Imitasi Pada Siswa Kelas VI SDN 2 Limboto Kabupaten Gorontalo - Dewi Harun (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
Writing poetry is one of the activities at school which is included in literacy activities. Literacyactivities can enrich students' knowledge and insight, especially in writing poetry. In order forstudents to be able to write poetry properly and correctly, it is necessary for the creativity of a teacherto create a learning innovation that can motivate students' enthusiasm for learning, knowledge andskills. The teacher must be able to innovate in learning so as to create meaningful learning forstudents and one of the innovations chosen is the selection of methods in learning. The purpose of thisstudy is to describe the results of learning innovation using imitation methods. The data generated inthe first cycle of 33 the number of grade VI students who are able to make poems properly are only0.39% and those who have not been able to make poems properly and correctly by 0.60% with bothpercentages of 0.21% . From the results of the first cycle, revisions were made for the implementationof the second cycle, so that in the second cycle learning an increase of 0.85% of students was able tomake poetry well and correctly, while students who were unable to 0.15% with a percentage of 0.70% The percentage increase between cycles I to II was 0.49%. So it is concluded that the imitationmethod is very good for use in language learning, especially poetry writing material.